Hubungan Konformitas Teman Sebaya dan Perilaku Bullying Pada Remaja Akhir - Ezra Addo Setiawan; Anniez Rachmawati Musslifah; Dhian Riskiana Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Adolescence is characterised by a process of transition from childhood to adulthood. During the transition period, adolescents will experience development in different aspects that are influenced by different factors, one of which is the environment. Adolescents spend most of their time in the school environment, so almost all adolescent development is influenced by their friends, which can be called peer conformity, which can have negative effects, one of which is bullying behaviour, which is currently widespread. This study aims to determine the relationship between peer conformity and bullying behaviour in late adolescence. This study uses a quantitative method with a total of 100 adolescents. The sampling technique used in this study was purposive sampling technique (late adolescents aged 15-18 years and still actively attending school), with data analysis using simple regression test and hypothesis testing which shows R square 0.01. The results of this study indicate a significant positive relationship between peer conformity and bullying behaviour, which means that the higher the peer conformity, the higher the bullying behaviour in adolescents.